IMPROVING STUDENTS’ READING COMPREHENSION ACHIEVEMENT THROUGH PQ4R STRATEGY TO THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 19 PALEMBANG - Elly Zuriah (Universitas PGRI Palembang, 2020)
This research study was carried out based on the problem faced by the writer as the teacher of English at SMAN 19 Palembang. The result of the preliminary study at the eleventh grade of SMAN 19 Palembang showed that the students’ reading comprehension achievement did not meet the standard criteria of success. To solve the problem, the writer decided to conduct classroom action research. The research problem of this research were “ How could PQ4R Strategy improve the students’ reading comprehension achievement to the eleventh-grade students of SMAN 19 Palembang?” and “What was the students’ perception of the implementation of PQ4R strategy to improve their reading comprehension achievement? This study was conducted in three cycles by following the procedure of classroom action research: planning, implementing, observing, and reflecting. The findings of the study showed that the PQ4R strategy could increase students’ reading comprehension achievement. It could be inferred that students’ perception was very good.